ПОНЯТТЯ І СТРУКТУРА ІНТЕЛЕКТУАЛЬНОГО КАПІТАЛУ: ЕВОЛЮЦІЯ І СУПЕРЕЧНІСТЬ ТРАКТУВАНЬ - Dyachenko, Yu.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper studies evolution of views on the concept «intellectual capital», finds the reasons why there are so different interpretations and structure of intellectual capital in the scientific literature.